Kasih Kasih dan Disiplin sebagai Dasar Pengasuhan Generasi Alpha: Analisis Amsal 13:24 - Christina Lauren Sihombing; Hermanto Hermanto (Student Evangelical Journal Aiming At Theological Interpretation, 2026)
Generation Alpha grows up in a highly dynamic digital environment, connected to technology from an early age. While this context offers various opportunities for the development of knowledge and skills, it also presents challenges regarding character formation, self-control, emotional development, and social relationships. Research on parenting Generation Alpha from a theological perspective based on Proverbs 13:24 remains relatively scarce. This study aims to analyze the theological meaning of Proverbs 13:24 and its relevance to parenting Generation Alpha amidst the advancement of digital technology. A qualitative research method was employed, utilizing a literature study approach that included lexical text analysis, an examination of the wisdom literature context, and theological reflection. The findings indicate that the term "rod" in Proverbs 13:24 serves as a symbol of parental authority, guidance, correction, and responsibility in child-rearing, rather than a justification for physical violence. These findings underscore the importance of integrating love, discipline, and wise authority to shape the character, spirituality, and moral responsibility of Generation Alpha.